Minor Groove Binder Probe Real-Time RT-PCR for Detection of Foot-and-Mouth Disease Virus in Egypt (Global Journal of Medical Research, 2019)
Shorter, more specific minor groove binders (MGBs) probes are dsDNA-binding agents attached to the 3′ end of Taq Man probes that could be designed strictly to the invariant region. Application and assessing of a new trend for viral detection in Egypt depending on MGB probe real-time RT-PCR (rRT-PCR) applied on local FMDV serotypes O, A, and SAT2. Moreover, FMDV O was detected using two serotype specific primer sets by SYBR Green real-time RT-PCR assaying rapid formats. The limit of detection of diluted RNAs using MGB probe rRT-PCR assay reached to ≤ 6 FG/ul. Besides, the high specificity of it was clear. In contrary, the employing of FMDV O specific primer pairs in SYBR Green real-time RT-PCR showed less sensitivity and specificity, particularly one of them displayed poor performance illustrating important cause of the false negative results in the conventional PCR. Lastly, the local financial cost of MGB probe is considered the obvious hinder in my country.
Keywords: foot-and-mouth disease virus; rRT-PCR; MGB probe